The impact of pharmacotherapy on sexual function in female patients being treated for idiopathic overactive bladder: a systematic review - Christopher Neal Bruce Evans; Anja Badenhorst; Frans Jacob Van Wijk (BMC, 2024)
Abstract Background Overactive bladder (OAB) is a condition defined by urgency with or without incontinence which disproportionately affects female patients and has a negative impact on sexual enjoyment and avoidance behaviour. Pharmacotherapy can be considered one of the main options for treating OAB. This research set out to determine the impact of pharmacotherapy on sexual function in females with OAB. Methods This research used the robust methodology of a systematic review. The clinical question was formulated using the PICO (population, intervention, control, and outcomes) format to include females being treated with pharmacotherapy (anticholinergics or beta-3 adrenergic agonists) for idiopathic OAB with the use of a validated questionnaire assessing self-reported sexual function at baseline and post-treatment. The review incorporated the MEDLINE, PubMed and EMBASE databases. The AMSTAR 2 (A Measurement Tool to Assess Systematic Reviews) appraisal tool was used to guide the review process. Two reviewers worked independently in screening abstracts, deciding on the inclusion of full-texts, data extraction and risk of bias assessment. Results In female patients with OAB, pharmacotherapy does seem to offer at least partial improvement in self-reported sexual function outcomes after 12 weeks of therapy. Still, the value of this finding is limited by an overall poor quality of evidence. Patients with a higher degree of bother at baseline stand to benefit the most from treatment when an improvement within this health-related quality of life domain is sought. Conclusion This research should form the basis for a well-conducted randomized controlled study to accurately assess sexual function improvements in females being treated with pharmacotherapy for OAB.